Effect of Activation by Alkaline Solution on Properties of Activated Carbon from Rubber Wood - CHUENKLANG, Phawik; THUNGTONG, Samran; VITIDSANT, Tharapong (Journal of Metals, Materials and Minerals, 2022)
This research is a study of the effect of activation by alkaline solution on the properties of activated carbon from rubber wood. The experiment included both carbonization and activation. The variables studied were a temperature range of 350-500°C and carbonized time (45, 60, 90, and 120 minutes) in the carbonization step. A suitable carbonization condition was at a temperature 400°C for 45 minutes with 27.51 % yield, 70.46 % fixed carbon, 25.90 % volatile matters and 2.32 % ash. Rubber wood char was activated by alkaline solution: KOH and NaOH. The variables were temperature, activation time and size of rubber wood char including the weight ratio of char per alkaline in the activation step. The experimental results were found to be that the suitable conditions for alkaline activation using both KOH and NaOH as activating agent was 700°C for 3 hours with rubber wood char size, 0.60-1.18 mm. Activated carbon prepared from KOH with a 1:1 ratio of char per alkaline gave higher quality than NaOH because stronger alkaline of NaOH developed larger pore sizes. The activated carbon obtained by KOH as an activating agent was 48% yield, 0.114 g/cm3 bulk density, 5.24% ash, iodine number 1069 mg/g, methylene blue number 202 mg/g and BET surface are 943 m2/g whereas NaOH gave lowers values of these properties.